PRODUCTION OF BACTERIAL CELLULOSE FROM LEMONGRASS KOMBUCHA - Jonathan Gilbert Alexis, Julio
Bacterial Cellulose (BC) is a recently sought-after natural polymer for use in various biomaterial applications. This is due to the superior structural strength and purity of BC compared to other types of cellulose. BC can be produced from kombucha fermentation in the form of a solid-state symbiotic culture of bacteria and yeast (SCOBY). In this research, several concentrations of lemongrass (10, 15, and 20g/L) and sugar (30, 50, and 70g/L) were used. Each variable were optimised using one-way ANOVA to determine the best combination within a 14 day-long incubation at 30?C. The best lemongrass and sugar combination was fermented for 21 days at 30?C with an initial SCOBY of 3% w/v and kombucha of 10% v/v. Microbial colonies were isolated and enumerated using single plate – serial dilution spotting (SP-SDS) before identification using MALDITOF-MS. Several chemical assays were performed once every 3 days: DNS spectrophotometry of total reducing sugars, Folin-Ciocalteu spectrophotometry of total phenolic content, titration of total organic acids, and direct pH measurement. SCOBY was purified using a 0,5M NaOH solution by the end of the incubation period to obtain pure BC before being analysed using EDS/SEM, FTIR, and XRD. Two species of yeast and one species of acetic acid bacteria were identified. A concentration of 10g/L lemongrass and 30g/L sugar yielded the most SCOBY at 56,82g/L. Total reducing sugar increased from 0,9 to 20,159g/L. Total organic acid increased from 0,018 to 0,342M, reducing pH from 2,8 to 2,065. Total phenolic compounds increased from 0,052 to 0,736g/L. BC sample has a mass percentage of 52,47% C, 42,35% O, 2,66% Na, and 2,51% Ca within a complex microfiber network. The structure consisted of ?1?4 glycosidic bonds with a crystallinity index of 67,23%. From this research, it is concluded that a concentration of 10g/L lemongrass and 30g/L sugar is optimum for BC production, with a final SCOBY yield of 56,82g/L.